Hadith #5864 - Sahih Muslim - Musa bin Anas bin Malik موسى بن أنس بن مالك (Sahih Muslim)
It never happened that Allah’s Messenger (ﷺ) was asked anything for the sake of Islam and he did not give that. There came to him a person and he gave him a large flock (of sheep and goats) and he went back to his people and said: My people, embrace Islam, for Muhammad gives so much charity as if he has no fear of want.
Grade: Sahih